Analisis Faktor yang Berhubungan dengan Pencegahan pada Anemia Remaja Putri di Pondok Pesantren Saadatul Abadiyah Kuala Tungkal Tahun 2022 - Yanti, Yanti; Siregar, Sarinah (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this study was to determine the analysis of factors related to the prevention of anemia in adolescent girls. This research is analytical with a cross sectional research design. The population of this study was all 65 class XI female students at the Saadatul Abadiyah Kuala Tungkal Islamic Boarding School. The data analysis used is univariate and bivariate analysis. The results of the research show that there is a relationship between knowledge, attitudes, peer influence and the role of health workers with the prevention of anemia in adolescent girls at the Saadatul Abadiyah Kuala Tungkal Islamic Boarding School during 2022.